SAKRAL-PROVAN DALAM PERSPEKTIF EPISTIMOLOGI BRAHMA WIDYA - I Putu Gede Parmajaya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Art in Hindu perspective in Bali has a very basic position, because it can not be separatedfrom the Hindu community relegius. Ceremonies in temples (holy places) also can not be separatedfrom the arts such as sound art, dance, karawitan, painting, fine arts, and literature. Temples,temples and others are built in such a way as an expression of the aesthetic, ethical, and religiousattitudes of the Hindus in Bali. Pragina or dancers in the spirit of ngayah or work withoutshowing pamelih various forms of art as a form of bhakti before Ida Sang Hyang Widhi Wasa(God Almighty). In it there is a sense of devotion and devotion as a form of longing to meet thesource of art itself and artists want to be one with the art because in fact every human being inthis world is a spark of art. Thus our knowledge of the art of sacred dance needs to be improved,so that we have the basis of penguuan and philosophical meaning of sacred and provan artform. This is important to do considering the essence of sacred art (especially) dance isincreasingly less understood by the Hindus, so it is feared over time the sacral dance will becomeprofane.